(untitled) (CAHIERS MAGELLANES-NS, 2024)
The present study aims to evaluate the effects of a polyherbal extract on sperm concentration, motility, and abnormalities in male albino rats. Polyherbal formulations, combining multiple medicinal plants, are traditionally used to address various health issues, including reproductive health. The study utilized a blend of clove buds (Syzygium aromaticum) and Triphala powder (a combination of Phyllanthus emblica, Terminalia belerica, and Terminalia chebula), administered at different dose levels of 200 mg/kg, 400 mg/kg, and 600 mg/kg body weight, to assess its impact on male reproductive parameters. Male albino rats were divided into four groups: a control group with normal saline, and remaining three treatment groups with the polyherbal extract at different doses for 30 days. Sperm concentration, motility, and abnormalities were evaluated in the epididymis after treatment. The polyherbal extract significantly reduced sperm concentration in a dose-dependent manner, with the highest dose (600 mg/kg) showing the most substantial decrease. Sperm motility also decreased with increasing doses, with the highest reduction observed at 600 mg/kg. Additionally, the extract led to increased sperm abnormalities, particularly in the head and tail regions, with the most pronounced effects at the highest dose. These findings indicate that the polyherbal extract exerts a dose-dependent impact on sperm parameters, leading to significant reductions in sperm concentration and motility, and an increase in sperm abnormalities. While these effects highlight the potent action of the extract, they also suggest potential adverse impacts on male reproductive health. Further studies are needed to explore the underlying mechanisms and safety of such polyherbal formulations in reproductive health.